Pancreatic Transdifferentiation Using β-Cell Transcription Factors for Type 1 Diabetes Treatment - Mahoney, Alexandra L. G.; Nassif, Najah T.; O’Brien, Bronwyn A.; Simpson, Ann M. (Cells (Basel, Switzerland), 2022)
Type 1 diabetes is a chronic illness in which the native beta (β)-cell population responsible for insulin release has been the subject of autoimmune destruction. This condition requires patients to frequently measure their blood glucose concentration and administer multiple daily exogenous insulin injections accordingly. Current treatments fail to effectively treat the disease without significant side effects, and this has led to the exploration of different approaches for its treatment. Gene therapy and the use of viral vectors has been explored extensively and has been successful in treating a range of diseases. The use of viral vectors to deliver β-cell transcription factors has been researched in the context of type 1 diabetes to induce the pancreatic transdifferentiation of cells to replace the β-cell population destroyed in patients. Studies have used various combinations of pancreatic and β-cell transcription factors in order to induce pancreatic transdifferentiation and have achieved varying levels of success. This review will outline why pancreatic transcription factors have been utilised and how their application can allow the development of insulin-producing cells from non β-cells and potentially act as a cure for type 1 diabetes.